Lesions in the nuo Operon, Encoding NADH Dehydrogenase Complex I, Prevent PurF-Independent Thiamine Synthesis and Reduce Flux through the Oxidative Pentose Phosphate Pathway in Salmonella enterica Serovar Typhimurium - Claas, Kathy (American Society for Microbiology, 2000)
In Salmonella enterica serovar Typhimurium, PurF-independent thiamine synthesis (or alternative pyrimidine biosynthesis) allows strains, under some growth conditions, to synthesize thiamine in the absence of the first step in the purine biosynthetic pathway. Mutations have been isolated in a number of loci that prevent this synthesis and thus result in an Apb(−) phenotype. Here we identify a new class of mutations that prevent PurF-independent thiamine synthesis and show that they are defective in the nuo genes, which encode the major, energy-generating NADH dehydrogenase of the cell. Data presented here indicated that a nuo mutant has reduced flux through the oxidative pentose phosphate pathway that may contribute to, but is not sufficient to cause, the observed thiamine requirement. We suggest that reduction of the oxidative pentose phosphate pathway capacity in a nuo mutant is an attempt to restore the ratio between reduced and oxidized pyridine nucleotide pools.